Development of an intraoral device for in situ biofilm study validated by its effective application in assessing biofilm characteristics - Abdullah, Nizam (2021)
Modelling and characterising in situ oral biofilm development have played an important role, particularly in cariology, in understanding the pathogenesis and prevention of the disease, and new product development for caries control. However, the currently available models for this purpose are far from satisfactory. Hence, the objectives of this study, conducted in two phases, was first, to develop and validate an intraoral device for in situ biofilm development in human subjects, and second, to evaluate the effect of two different chemical stressors, silver diamine fluoride (SDF) and potassium iodide (KI), clinically used for caries control, on in situ plaque biofilms developed, using the validated device. In Phase one, a novel, acrylic, intra oral device carrying multiple transparent removable wells that could be comfortably worn by subjects was fabricated. To validate the device, an in vivo study was conducted to compare the microbial viability and composition between device-formed, and tooth-formed biofilms, using viability polymerase chain reaction (vPCR) and next generation sequencing (NGS) respectively. Structural characteristics of device-formed biofilm was analysed by confocal laser scanning microscopy (CLSM). In phase two, the device, thus validated, was utilized to compare the antibacterial efficacy of SDF and KI either singly or in combination, on device-formed, standardized, plaque biofilm. Multiple, device-formed in situ plaque biofilm samples were collected from six healthy subjects over 4 to 24 hr, for investigating various outcomes. The new device developed was economical, simple to fabricate, and permitted easy insertion and removal by the subjects. Results showed no significant quantitative difference in viable bacteria between device-formed and tooth-formed biofilms (p > 0.05). The data revealed no significant difference between device-formed and tooth-formed plaque biofilms with regards to intraoral location of the device. However, comparison among subjects revealed significant differences in all viability parameters evaluated (p < 0.05). Furthermore, analysis of 24 hr in situ device-formed biofilm, under CLSM showed heterogenous biofilm configurations. On NGS analyses a total of 10 major bacterial genera were identified in both device-formed and tooth-formed biofilms and comprised: Streptococcus, Neisseria, Haemophilus, Rothia, Prevotella, Fusobacterium, Veilonella, Actinomyces, Clostridium sensustricto and Corynebacterium. In terms of chemical stressors, SDF and KI in combination had no significant anti-biofilm effect on in situ anti-plaque biofilm activity, compared with SDF or KI, alone (p < 0.05). To conclude, a novel, simple, intraoral device to study in situ biofilm development in human subjects was developed and validated. In clinical terms, the use of chemical stressors SDF and KI, either singly or in combination, appear to yield a similar anti-plaque biofilm effect.